How to Stop Jihadist Foreign Fighters. (Political Science Quarterly (Oxford University Press / USA))
The article examines the counterterrorism efforts that aim to stop jihadist foreign fighters. Topics discussed include the key role of foreign fighters in such major jihadist terrorist plots in the West as the al Qaeda attacks on U.S. embassies in Africa in 1998 and the September 11, 2001 terrorist attacks, counterterrorism strategies that influence the production cycle of foreign fighters, namely, preventing recruitment, disrupting travel and tracking fighters, and the need for political leaders to ensure community support to pursue terrorists after a terrorist attack.